2011
DOI: 10.1117/12.882536
|View full text |Cite
|
Sign up to set email alerts
|

Methods for prediction of refractive index in glasses for the infrared

Abstract: It is often useful to obtain custom glasses that meet particular requirements of refractive index and dispersion for highend optical design and applications. In the case of infrared glasses, limited experimental data are available due to difficulties in processing of these glasses and also measuring refractive indices accurately. This paper proposes methods to estimate refractive index and dispersion as a function of composition for selected infrared-transmitting glasses. Methods for refractive index determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…[31][32][33][34] More recently, McCloy used the Gladstone-Dale relation on heavy metal oxide glasses, where an incident wavelength in the infrared was used to determine the index of refraction of the glasses. 35 This is very different from the experiments of the past that were largely done on silicate-based glasses with the use of the sodium D line. Using the Gladstone-Dale relation, he found that the resulting index-of-refraction values for heavy metal oxide glasses matched fairly well with the measured index of refraction.…”
Section: Applications In Oxide Glass Chronologymentioning
confidence: 81%
“…[31][32][33][34] More recently, McCloy used the Gladstone-Dale relation on heavy metal oxide glasses, where an incident wavelength in the infrared was used to determine the index of refraction of the glasses. 35 This is very different from the experiments of the past that were largely done on silicate-based glasses with the use of the sodium D line. Using the Gladstone-Dale relation, he found that the resulting index-of-refraction values for heavy metal oxide glasses matched fairly well with the measured index of refraction.…”
Section: Applications In Oxide Glass Chronologymentioning
confidence: 81%
“…The refractivity values obtained here can provide a reasonable estimate of a novel composition's refractive index; however, the LL model does not consistently predict transition points, or extrema, along the tielines. The reasoning for this is due to the model only considering elemental refractivity contributions and ignoring contributions from specific structures or bond types, such as the shifts observed at stoichiometry and when Ge 2 Se 6/2 ethane‐like modes appear, as has been noted previously by McCloy . Other approaches such as band–orbital theory and ab initio modeling do not presuppose a purely intra‐atomic (or intra‐ionic) response and could therefore provide a more complete explanation.…”
Section: Resultsmentioning
confidence: 99%
“…The reasoning for this is due to the model only considering elemental refractivity contributions and ignoring contributions from specific structures or bond types, such as the shifts observed at stoichiometry and when Ge 2 Se 6/2 ethane-like modes appear, as has been noted previously by McCloy. 46 Other approaches such as band-orbital theory 47,48 and ab initio modeling 49 do not presuppose a purely intra-atomic (or intra-ionic) response and could therefore provide a more complete explanation. However, these methods were outside the scope of the current analysis.…”
Section: Modeling Of Optical Propertiesmentioning
confidence: 99%
“…Various physical properties including molecular weight (M), density (ρ), refractive index (n), molar volume (V m ), packing density (PD), rare earth-ion concentration (N), polaron radius (r p ) and critical distance (R c ) for Eu 3+ doped borogermanate glasses have been provided in Table 1. The refractive indexes of glasses have been calculated using Gladstone-Dale relation [28]. The critical distances (R c ) and other calculated physical properties of glasses have been obtained according to literature [29,30], respectively.…”
Section: Resultsmentioning
confidence: 99%